PELATIHAN DIGITAL MARKETING SEBAGAI UPAYA PENGEMBANGAN KETERAMPILAN PELAKU UMKM DI POLOKARTO, SUKOHARJO - Atur Semartini; Alip Desi Suyono Saputri (LPPM Institut Pendidikan Nusantara Global, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the welfare of society and in economic development in many countries, including Indonesia. However, in practice, MSMEs often face obstacles in advancing and growing their businesses. One common challenge is in product promotion. This Community Service activity aims to provide knowledge and training to MSME actors in Polokarto village regarding digital marketing to help them promote their businesses more widely. This activity was conducted through counseling and training methods, which also facilitated discussions between the participants and the service team. Before the activity began, participants were given a pre-test to assess their initial knowledge of digital marketing. After the activity concluded, a post-test was administered to evaluate the increase in knowledge. Based on the pre-test and post-test results, there was an average score increase of 28.750. Additionally, based on data analysis, a p-value of < 0.05 was obtained. This indicates that the counseling and training had a significant impact on participants’ knowledge of digital marketing. With this digital marketing training and counseling, MSME actors can overcome promotional challenges, making their products more widely known and enabling them to survive in a competitive market.